1999
DOI: 10.1016/s0928-8244(99)00005-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis serotype H34 isolated from human and insecticidal strains serotypes 3a3b and H14 can lead to death of immunocompetent mice after pulmonary infection

Abstract: In 1995, we isolated a strain of Bacillus thuringiensis serotype H34 from severe human tissue necrosis. This bacterium was able to induce myonecrosis in immunosuppressed mice after cutaneous infection. Its potential pathogenicity for immunocompetent hosts was investigated in a mouse model of pulmonary infection. Mice infected intranasally by a suspension containing 10(8) spores died within 8 h in a clinical toxic-shock syndrome. In the same conditions, infection with a mutant without crystalline toxin, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 4 publications
3
57
0
Order By: Relevance
“…The cause of death is unknown, and, in mice, it is unlikely to be due to the growth of the bacteria. However, as previously described (Hernandez et al, 1999), the syndromes observed in infected mice suggest that haemolysin production may be involved in death. These opportunistic properties have been lost (or highly reduced) in the ∆plcR mutants of the B. thuringiensis and B. cereus strains used in this study, and they are also absent from a B. anthracis vaccine strain known to be defective in PlcR activity (Agaisse et al, 1999).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The cause of death is unknown, and, in mice, it is unlikely to be due to the growth of the bacteria. However, as previously described (Hernandez et al, 1999), the syndromes observed in infected mice suggest that haemolysin production may be involved in death. These opportunistic properties have been lost (or highly reduced) in the ∆plcR mutants of the B. thuringiensis and B. cereus strains used in this study, and they are also absent from a B. anthracis vaccine strain known to be defective in PlcR activity (Agaisse et al, 1999).…”
Section: Discussionsupporting
confidence: 62%
“…Nasal instillation of 10) or 5i10( spores of the 407 Cry − strain and of the B. cereus strain per mouse rapidly resulted in high mortality rates (Table 1). Mice died within 24 h, with syndromes similar to those described for the B. thuringiensis strain konkukian (Hernandez et al, 1999). However, instillation of 10( spores per mouse in the same volume (50 µl) resulted in no deaths with 407 Cry − spores and a high mortality rate with the B. cereus strain, which suggests that the two strains differ in pathogenicity.…”
Section: Cytotoxic and Haemolytic Activities Are Controlled By Plcrmentioning
confidence: 63%
See 1 more Smart Citation
“…thuringiensis and B. cereus establish persistent infections with infiltration of phagocytes, implying that the bacteria circumvent the host immune system (2,14,31). However, interactions between the host immune cells and these bacteria are still poorly characterized, and how they resist the immune defense system remains unknown.…”
mentioning
confidence: 99%
“…Moreover, a B. cereus strain has caused lethal infections resembling anthrax (36), and several cases of bacteremia in preterm neonates have been described, highlighting this public health problem (35,49). Infections are characterized by bacterial accumulation despite the induction of inflammation (33,34). Therefore, B. cereus is able to persist and to counteract the host immune system.…”
mentioning
confidence: 99%